2019
DOI: 10.3389/fimmu.2019.00887
|View full text |Cite
|
Sign up to set email alerts
|

Restored and Enhanced Memory T Cell Immunity in Rheumatoid Arthritis After TNFα Blocker Treatment

Abstract: TNFα inhibitors have shaped the landscape of rheumatoid arthritis (RA) therapy with high clinical efficiency. However, their impact on T cell recall responses is not well-elucidated. We aimed to analyze the immune profiles of memory T cells in RA patients undergoing TNFα inhibitor Golimumab (GM) treatment. Frequencies of peripheral T cell subsets and cytokine expression profiles in memory T cells (T M ) upon PMA/Ionomycine stimulation were determined by flow cytometry. Antigen-specific C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…3A). An increased fraction of CD8+ T cells following anti-TNF treatment has also been recently described in RA patients [34]. The analysis also indicated that TNF-blockers may skew monocyte/macrophage polarization towards an M2 regulatory phenotype (Fig.…”
Section: Menegatti Et Al Have Recently Investigated the Global Impact Of Tnfi On Immune Responses Tosupporting
confidence: 69%
See 1 more Smart Citation
“…3A). An increased fraction of CD8+ T cells following anti-TNF treatment has also been recently described in RA patients [34]. The analysis also indicated that TNF-blockers may skew monocyte/macrophage polarization towards an M2 regulatory phenotype (Fig.…”
Section: Menegatti Et Al Have Recently Investigated the Global Impact Of Tnfi On Immune Responses Tosupporting
confidence: 69%
“…Increased effector responses after TNFi treatment has also been observed in RA patients (Table 2). Patients treated with golimumab showed an increase in the CD8+ T cell effector population, accompanied by increased responses to viral antigens, suggesting that TNF blockade, while broadly suppressing inflammation, does not induce generalized immunosuppression, but rather may "normalize" immune responses [34]. In agreement with this concept, anti-TNF treatment did not affect the expression of TNF-inducible genes in the site of acute inflammatory challenge (tuberculin injection), while decreasing the inducibility of these genes in blood samples [116].…”
Section: Cellular Profilingmentioning
confidence: 99%
“…As expected, there was a significant reduction of IL‐1β, IL‐6, and TNF‐α concentration in sera of CIA mice administrated with MB‐3 (Figure 3B). Previous studies showed that these proinflammatory cytokines were important in T cell proliferation and polarization, which contributed to the progress of RA 22,23 . Flow cytometric analysis revealed the reduction in both CD4 + and CD8 + T cell population that highly expressed CD44, a marker of murine memory T cells from MB‐3‐treated CIA mice (Figures 3C and D).…”
Section: Resultsmentioning
confidence: 80%
“…Previous studies showed that these proinflammatory cytokines were important in T cell proliferation and polarization, which contributed to the progress of RA. 22 , 23 Flow cytometric analysis revealed the reduction in both CD4 + and CD8 + T cell population that highly expressed CD44, a marker of murine memory T cells from MB‐3‐treated CIA mice (Figures 3C and D ). The imbalance between proinflammatory and anti‐inflammatory T cells populations dysregulated in RA leading to severe clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, MALT1 was observed to reduce longitudinally during treatment, whose reduction correlated with RA treatment outcome (treatment response, low disease activity, or disease remission), which was in line with the previous study in IBD patients ( 14 ). The explanations are: (1) during treatment, the inflammation of RA is attenuated, then MALT1 closely relates to RA inflammation, so MALT1 is decreased together with inflammation ( 12 , 14 , 20 ); (2) bDMARDs or csDMARDs treatment may regulate multiple immune cells to affect MALT1 level in patients ( 29 , 30 ). The above data indicated the value of MALT1 measurement as a marker for disease monitoring of RA.…”
Section: Discussionmentioning
confidence: 99%